2016
DOI: 10.2135/cropsci2015.05.0331
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Fine Mapping of SiDWARF2 (D2) in Foxtail Millet

Abstract: Elongation of grass internodes determines the plant height and underlies the grain yield of grass crop species, by enhancing of lodging resistance in elite cultivars. Foxtail millet [Setaria italica (L.) P. Beauv.] is an ancient cereal crop that served as a staple food during early civilization in China and is still grown widely across South and East Asia, Europe, and Africa. In this study, a foxtail millet dwarf mutant (Sidwarf2), derived from ‘Yugu1’, was characterized. In the dwarf mutant, significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…This type of pleiotropic effect of dwarfing genes has also been observed in other crop species (Duan et al, 2012; Zhang et al, 2014a; Chen et al, 2015; Jin et al, 2015; Liu et al, 2015). In Setaria, Sidwarf2 ( D2 ) has also been characterized as a mutant with multitrait variations (Xue et al, 2016), and many dwarf mutants identified in Setaria (Ratnaswamy and Dhanaraj, 1961; Yao and Liang, 1990; Dineshkumar et al, 1992) were the result of shortened internodes with no change in the number of internodes. Interestingly, only one previously reported mutant in rice, nl1 , has ever been identified as having a changed number of stem internodes (Wang et al, 2009), which was similar to Sidwarf3 , suggesting that dwarfism involving changed internode number may be conditioned by specific regulators in plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of pleiotropic effect of dwarfing genes has also been observed in other crop species (Duan et al, 2012; Zhang et al, 2014a; Chen et al, 2015; Jin et al, 2015; Liu et al, 2015). In Setaria, Sidwarf2 ( D2 ) has also been characterized as a mutant with multitrait variations (Xue et al, 2016), and many dwarf mutants identified in Setaria (Ratnaswamy and Dhanaraj, 1961; Yao and Liang, 1990; Dineshkumar et al, 1992) were the result of shortened internodes with no change in the number of internodes. Interestingly, only one previously reported mutant in rice, nl1 , has ever been identified as having a changed number of stem internodes (Wang et al, 2009), which was similar to Sidwarf3 , suggesting that dwarfism involving changed internode number may be conditioned by specific regulators in plants.…”
Section: Discussionmentioning
confidence: 99%
“…A bulked segregant analysis, followed by map‐based cloning, is a powerful tool for gene isolation in model plants, such as Arabidopsis and rice. In Setaria, this approach was found to be efficient for rapid mapping of favorable loci (Li et al, 2016; Liu et al, 2016; Xue et al, 2016). A MutMap method was developed on the basis of high‐throughput genome resequencing techniques (Abe et al, 2012; Fekih et al, 2013; Takagi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QTL-seq was useful not only for analysis of QTL but also for a gene for qualitative traits between cultivars. For construction of linkage Wang et al 1998;Jia et al 2009;Sato et al 2013), QTL of morphological/agronomic traits (Doust et al 2004(Doust et al , 2005Mauro-Herrera et al 2013) and positional cloning (Li et al 2015;Xue et al 2016), combinations between distantly related parents such as between a S. italica cultivar and the wild ancestor, ssp. viridis, between a Japanese landrace and a Taiwanese landrace and between divergent Chinese cultivars have been used.…”
Section: Re-sequencing and Qtl-seq Of Nekodementioning
confidence: 99%
“…The high-quality genome sequence of foxtail millet has also allowed in-depth analyses of transposon family dynamics and locations that reveal hitherto unsuspected variation between transposon families in insertion site preference and turnover (Bennetzen et al, 2016). Mutant populations have been characterized in both foxtail millet and green foxtail millet, and the identity of candidate genes was revealed by novel high-throughput sequencing approaches (Li et al, 2016; Liu et al, 2016; Martins et al, 2016; Xue et al, 2016). S. italica and S. viridis have been used in the characterization of important agronomic traits, including yield-related architectural traits such as height, branching, biomass, flowering time and domestication-related traits such as shattering (Qian et al, 2012; Jia et al, 2013; Mauro-Herrera et al, 2013; Wang et al, 2013; Doust et al, 2014; Gupta et al, 2014; Layton and Kellogg, 2014; Qie et al, 2014; Fahlgren et al, 2015; Fang et al, 2016; Hodge and Kellogg, 2016; Liu et al, 2016; Mauro-Herrera and Doust, 2016).…”
mentioning
confidence: 99%